Iridium compound and preparation method and application thereof
By mixing the iridium-containing compound with concentrated nitric acid and passing it into NO gas, a high-purity iridium complex nitrosyl nitrite iridium without halogen was prepared, which solved the problem of the existing iridium materials being incorporated into harmful elements during the preparation process, and achieved the It has high purity and stability of iridium materials, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411514322.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
During the preparation process, existing iridium materials are easily incorporated with harmful elements such as halogen, resulting in a decrease in their activity, high temperature resistance and service life.
By mixing the iridium-containing compound with concentrated nitric acid and oxidizing treatment, an iridium nitrate solution was obtained, and NO gas was introduced therein, and a coordination reaction was carried out to obtain a high-purity iridium complex nitrosoyl nitric acid, which is free of halogen.
The high purity and stability of iridium material are achieved, the conversion rate of metal iridium reaches 100%, and the process flow of this method is simple, low cost, and suitable for industrial production.
Smart Images

Figure CN119392293A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode material precursors, and specifically relates to an iridium compound and a preparation method and application thereof, and an iridium-tantalum-titanium electrode material. Background Art
[0002] Iridium is an important metal element, which has important applications in aerospace, medicine, chemical industry and other fields. Iridium materials containing iridium and other metals (such as iron, tantalum, titanium) or non-metallic elements (such as carbon, nitrogen) are widely used in the preparation of hydrazine decomposition catalysts, anode materials for electrolysis of water to produce hydrogen, anode materials in the chlor-alkali industry, etc. When preparing iridium materials, the raw materials used are mainly halogen-containing iridium compounds (such as chloroiridic acid, iridium trichloride, iridium tetrachloride and iridium tribromide). However, existing studies have shown that if harmful elements such as halogens are added to the raw materials for the preparation of iridium materials, the activity, high temperature resistance and service life of the iridium materials will be greatly reduced. Therefore, it is imperative to develop new iridium materials that do not contain harmful elements. Summary of the invention
[0003] The purpose of the present invention is to provide an iridium complex and its preparation method and application, and an iridium-tantalum-titanium electrode material. The present invention uses iridium nitrate solution and NO to synthesize a high-purity, stable iridium complex that does not contain harmful elements such as halogens, and the conversion rate of metal iridium reaches 100%, which can be used as a precursor for preparing electrode materials and catalysts.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing an iridium complex, comprising the following steps:
[0006] Mixing an iridium-containing compound with concentrated nitric acid and performing an oxidation treatment to obtain an iridium nitrate solution; the iridium-containing compound includes an organic iridium complex or iridium iodide;
[0007] NO is introduced into the iridium nitrate solution to carry out coordination reaction to obtain the iridium complex; the iridium complex contains iridium ions, nitrosyl groups and nitrate groups; the flow rate of NO is 10-20 mL / min.
[0008] Preferably, the organic iridium complex comprises at least one of tri(oxalato)iridium(III) acid, iridium acetate and iridium acetylacetonate; and the iridium iodide is iridium triiodide or iridium tetraiodide.
[0009] Preferably, the concentration of the concentrated nitric acid is 6-8 mol / L; the usage ratio of the iridium-containing compound to the concentrated nitric acid is 5000 g: 3-5 L.
[0010] Preferably, the oxidation treatment is carried out at a temperature of 90 to 100° C. and for a time of 1 to 2 hours.
[0011] Preferably, when the iridium-containing compound is an organic iridium complex, the oxidation treatment is carried out in an O3 atmosphere, and the flow rate of O3 is 10 to 30 mL / min.
[0012] Preferably, the mass fraction of the iridium nitrate solution is 40-60%; the temperature of the coordination reaction is 70-90° C., and the time is 10-30 min.
[0013] The present invention provides an iridium complex obtained by the preparation method described in the above technical solution; the iridium complex is iridium nitrosyl nitrate, and the chemical formula is Ir(NO)(NO3)3(H2O)2.
[0014] The present invention provides the use of the iridium complex described in the above technical solution in catalysts or electrode materials.
[0015] The present invention provides an iridium-tantalum-titanium electrode material, comprising a titanium electrode material and an iridium-tantalum composite film layer on the surface of the titanium electrode material; the surface of the iridium-tantalum composite film layer has a polyhedral columnar structure; the iridium-tantalum composite film layer is obtained by mixing an iridium complex and tantalum ethoxide and then calcining, and the iridium complex is the iridium complex described in the above technical solution.
[0016] Preferably, the mass ratio of the iridium complex to tantalum ethoxide is 1:3-5; the calcination temperature is 600-700° C., and the holding time is 4-6 hours.
[0017] The invention provides a method for preparing an iridium complex, comprising the following steps: mixing an iridium-containing compound with concentrated nitric acid, performing oxidation treatment, and obtaining an iridium nitrate solution; the iridium-containing compound comprises an organic iridium complex or iridium iodide; passing NO into the iridium nitrate solution, performing coordination reaction, and obtaining the iridium complex; the iridium complex comprises iridium ions, nitrosyl groups, and nitrate groups; and the flow rate of the NO is 10 to 20 mL / min. In the present invention, concentrated nitric acid can realize the decomposition of organic ligands of the organic iridium complex, and can also oxidize iodine anions into iodine elements, thereby promoting the combination of iridium ions and nitrate ions to generate iridium nitrate, and the iridium nitrate solution obtained thereby substantially does not contain harmful elements such as halogens, and has high purity. On this basis, the present invention introduces nitrosyl groups by passing NO gas into an iridium nitrate solution to obtain an iridium complex containing both nitrosyl groups and nitrate groups, wherein the raw materials used in the present invention are green, environmentally friendly, cheap and easy to obtain, and other metal impurities and harmful elements such as halogens, sulfur, and phosphorus are not introduced during the preparation of the iridium complex, and the conversion rate of metal iridium reaches 100%; at the same time, the presence of nitrosyl groups makes the iridium complex have good stability, is not easy to decompose, and can stably exist in aqueous solution and solid state. Therefore, the present invention synthesizes an iridium complex with high purity and good stability, which can be used as a precursor for preparing electrode materials and catalysts. The process flow of the method described in the present invention is simple, the cost is low, and it is suitable for clean, efficient, and industrialized production of iridium complexes.
[0018] Further, the iridium-containing compound used in the present invention is cheap and easy to obtain, which reduces the preparation cost of iridium nitrate solution; when the iridium-containing compound is an organic iridium complex such as tri(oxalate)iridium(III) acid and iridium acetate, the present invention uses concentrated nitric acid and ozone combined oxidation to completely decompose the organic ligand of the organic iridium complex into water and carbon dioxide, and the iridium ion and nitrate are combined to generate iridium nitrate; when the iridium-containing compound is iridium iodide, the present invention uses concentrated nitric acid to oxidize iodine anions into iodine element, wherein the iodine element can be collected by sublimation-condensation, and the iridium ion and nitrate ion are combined to generate iridium nitrate. The synthesis method of iridium nitrate solution of the present invention is simple to operate and low in cost, and the iridium nitrate solution obtained thereby is substantially free of impurity elements such as halogen, sulfur, phosphorus and other metals, and does not need to perform cumbersome impurity removal operations, which is conducive to industrial production.
[0019] Furthermore, the iridium complex obtained according to the preparation method provided by the present invention is iridium nitrosyl nitrate, and its chemical formula is Ir(NO)(NO3)3(H2O)2. The present invention uses iridium nitrosyl nitrate and tantalum ethoxide as raw materials to prepare an iridium tantalum composite film layer on the surface of a titanium electrode material, that is, to obtain an iridium tantalum titanium anode material. In an embodiment of the present invention, the prepared iridium tantalum titanium anode material is characterized, and a scanning electron microscope (SEM) image shows that the surface of the iridium tantalum titanium anode material is uniform and dense, and has a polyhedral columnar structure. This polyhedral columnar structure can increase the surface area of the electrode material and increase the active sites; and because the iridium tantalum titanium anode material does not contain harmful elements such as halogens, sulfur or phosphorus, the activity, high temperature resistance and service life of the iridium tantalum titanium anode material are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 is a flow chart for the preparation of iridium nitrosyl nitrate;
[0022] Figure 2 This is the infrared spectrum of iridium nitrosyl nitrate obtained in Example 1;
[0023] Figure 3 This is the SEM image of the iridium tantalum titanium anode material. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing an iridium complex, comprising the following steps:
[0025] Mixing an iridium-containing compound with concentrated nitric acid and performing an oxidation treatment to obtain an iridium nitrate solution; the iridium-containing compound includes an organic iridium complex or iridium iodide;
[0026] NO is introduced into the iridium nitrate solution to carry out coordination reaction to obtain the iridium complex; the iridium complex contains iridium ions, nitrosyl groups and nitrate groups; the flow rate of NO is 10-20 min / L.
[0027] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0028] The present invention mixes an iridium-containing compound with concentrated nitric acid and performs oxidation treatment to obtain an iridium nitrate solution. In the present invention, the iridium-containing compound includes an organic iridium complex or iridium iodide.
[0029] In the present invention, the organic iridium complex may include at least one of tris(oxalato)iridium(III) acid, iridium acetate and iridium acetylacetonate; in an embodiment of the present invention, the organic iridium complex may be tris(oxalato)iridium(III) acid, iridium acetate or iridium acetylacetonate. In the present invention, the chemical formula of tris(oxalato)iridium(III) acid is H3Ir(C2O4)3, which is mentioned on page 310 of the Handbook of Synthesis of Precious Metal Compounds and Complexes compiled by Yu Jianmin.
[0030] When the iridium-containing compound is an organic iridium complex, the oxidation treatment is carried out in an O3 atmosphere. That is, the preparation method of the iridium nitrate solution of the present invention may include the following steps: mixing the iridium-containing compound with concentrated nitric acid, introducing O3, and performing oxidation treatment to obtain the iridium nitrate solution. In the present invention, the concentration of the concentrated nitric acid may be 6-8 mol / L; in an embodiment of the present invention, the concentration of the concentrated nitric acid may be 6 mol / L, 7 mol / L or 8 mol / L. In the present invention, the dosage ratio of the organic iridium complex to concentrated nitric acid may be 5000 g: 3-5 L; in an embodiment of the present invention, the molar ratio of the organic iridium complex to nitric acid in concentrated nitric acid is 5000 g: 3 L, 5000 g: 4 L or 5000 g: 5 L. In the present invention, the flow rate of O3 may be 10-30 mL / min; in an embodiment of the present invention, the flow rate of O3 may be 10 mL / min, 20 mL / min or 30 mL / min. In an embodiment of the present invention, concentrated nitric acid is dripped into the organic iridium complex under stirring, and then O3 is introduced into the system. When the concentrated nitric acid starts to be dripped, the temperature is uniformly raised to the temperature required for oxidation treatment and kept constant; the timing starts from the completion of the dripping of concentrated nitric acid, and the reaction is carried out under the temperature conditions required for oxidation treatment. The temperature of the oxidation treatment of the present invention can be 90-100°C; in an embodiment of the present invention, the temperature of the oxidation treatment can be 90°C, 95°C or 100°C. The time of the oxidation treatment of the present invention can be 1-2h; in an embodiment of the present invention, the time of the oxidation treatment can be 1h, 1.5h or 2h. The oxidation treatment of the present invention can be carried out under reflux conditions. In the present invention, after the oxidation treatment is completed, nitrogen oxides and carbon dioxide are also generated in the reaction system; the nitrogen oxides and carbon dioxide are introduced into an alkaline aqueous solution for tail gas treatment. In an embodiment of the present invention, the alkaline aqueous solution can be an aqueous sodium hydroxide solution, and the concentration of the aqueous sodium hydroxide solution can be 30wt%. In the present invention, the mass fraction of the iridium nitrate solution can be 40-60%; in the embodiment of the present invention, the mass fraction of the iridium nitrate solution is 40%, 50% or 60%. The present invention uses concentrated nitric acid and ozone to fully oxidize the organic ligand in the organic iridium complex to produce water and carbon dioxide, and the iridium ions and nitrate ions are combined to form iridium nitrate. The synthesis method of the iridium nitrate solution of the present invention is simple to operate and low in cost. The iridium nitrate obtained thereby substantially does not contain impurity elements such as halogen, sulfur, phosphorus and other metals, and does not require cumbersome impurity removal operations, which is conducive to industrial production.
[0031] In the present invention, the iridium iodide may be iridium triiodide or iridium tetraiodide.
[0032] When the iridium-containing compound is iridium iodide, the preparation method of the iridium nitrate solution may include the following steps: mixing the iridium-containing compound with concentrated nitric acid, performing oxidation treatment, and obtaining the iridium nitrate solution. In the present invention, the molar ratio of the iridium iodide to the nitric acid in concentrated nitric acid may be 1:3-6; in an embodiment of the present invention, the molar ratio of the iridium iodide to the nitric acid in concentrated nitric acid may be 1:3, 1:4, 1:5 or 1:6. In the present invention, the concentration of the concentrated nitric acid may be 6-8 mol / L; in an embodiment of the present invention, the concentration of the concentrated nitric acid may be 6 mol / L, 7 mol / L or 8 mol / L. In an embodiment of the present invention, specifically, under stirring, concentrated nitric acid is dripped into iridium iodide, and the temperature is uniformly increased to the temperature required for oxidation treatment and maintained at a constant temperature while the concentrated nitric acid begins to drip; the timing is started from the completion of the dripping of concentrated nitric acid, and the reaction is carried out under the temperature conditions required for oxidation treatment. The temperature of the oxidation treatment in the present invention may be 90-100°C; in an embodiment of the present invention, the temperature of the oxidation treatment may be 90°C, 95°C or 100°C. The oxidation treatment time of the present invention can be 1 to 2 hours; in the embodiment of the present invention, the oxidation treatment time can be 1 hour, 1.5 hours or 2 hours. The oxidation treatment of the present invention can be carried out under reflux conditions. In the present invention, after the oxidation treatment is completed, nitrogen oxides and iodine vapor are also generated in the reaction system; the nitrogen oxides can be introduced into an aqueous solution of alkali for tail gas treatment, and the iodine vapor is collected by condensation. In the embodiment of the present invention, the aqueous solution of alkali is a sodium hydroxide aqueous solution, and the concentration of the sodium hydroxide aqueous solution can be 30wt%. In the present invention, the mass fraction of the iridium nitrate solution can be 40 to 60%; in the embodiment of the present invention, the mass fraction of the iridium nitrate solution is 40%, 50% or 60%. The present invention oxidizes iridium iodide by concentrated nitric acid, oxidizes iodine anions to iodine element (iodine element can be removed by condensation), and iridium ions and nitrate ions combine to form iridium nitrate. The synthesis method of the iridium nitrate solution of the present invention is simple to operate and low in cost. The iridium nitrate solution obtained thereby substantially does not contain impurity elements such as halogen, sulfur, phosphorus and other metals, and does not require cumbersome impurity removal operations, which is conducive to industrial production.
[0033] After obtaining the iridium nitrate solution, the present invention passes NO into the iridium nitrate solution to carry out a coordination reaction to obtain the iridium complex. In the present invention, the flow rate of NO is 10 to 20 mL / min; in an embodiment of the present invention, the flow rate of NO is 10 mL / min, 15 mL / min or 20 mL / min. The temperature of the coordination reaction of the present invention can be 70 to 90°C; in an embodiment of the present invention, the temperature of the coordination reaction is 70°C, 75°C, 80°C, 85°C or 90°C. The time of the coordination reaction of the present invention can be 10 to 30 minutes; in an embodiment of the present invention, the time of the coordination reaction is 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.
[0034] In the present invention, after the coordination reaction is completed, the obtained liquid is concentrated to obtain an iridium complex. In the present invention, the concentration can be evaporation concentration; the evaporation concentration temperature can be 60-70°C; in an embodiment of the present invention, the evaporation concentration temperature is 60°C, 65°C or 70°C.
[0035] The present invention also provides an iridium complex obtained by the preparation method described in the above technical solution; the iridium complex is iridium nitrate, and the chemical formula is Ir(NO)(NO3)3(H2O)2. In the present invention, the mass content of iridium in the iridium nitrate is 44-46%; in the embodiment of the present invention, the mass content of iridium in the iridium nitrate is 45.10%, 45.19%, 45.23% or 45.25%. In the present invention, the conversion rate of iridium is 100%. The metal element impurities in the iridium nitrate solid prepared in the embodiment of the present invention are extremely low, and the content of elements such as Pb, Na, Mg, and Rh is less than 0.001%, and the content of elements such as Fe, Cu, Pt, and Si does not exceed 0.002%.
[0036] The invention does not introduce halogen ions and other metal ions during the synthesis process of the iridium complex, does not require complicated impurity removal steps, and the obtained iridium complex has high purity, the conversion rate of metal iridium reaches 100%, and is suitable for large-scale industrial production.
[0037] The present invention also provides the use of the iridium complex described in the above technical solution in catalysts or electrode materials.
[0038] The present invention also provides an iridium-tantalum-titanium electrode material, comprising a titanium electrode material and an iridium-tantalum composite film layer on the surface of the titanium electrode material. In the present invention, the surface of the iridium-tantalum composite film layer has a polyhedral columnar structure. In the present invention, the iridium-tantalum composite film layer is obtained by mixing an iridium complex and tantalum ethoxide and then calcining, and the iridium complex is the iridium complex described in the above technical solution.
[0039] In the present invention, the preparation method of the iridium tantalum titanium electrode material may include the following steps: mixing an iridium complex, tantalum ethoxide and a solvent and coating the mixture on a titanium electrode material, and then calcining the mixture to form an iridium tantalum composite film layer on the surface of the titanium electrode material to obtain the iridium tantalum titanium electrode material.
[0040] In the present invention, the mass ratio of the iridium complex to tantalum ethoxide may be 1:3-5; in an embodiment of the present invention, the mass ratio of the iridium complex to tantalum ethoxide is 1:3, 1:3.5, 1:4, 1:4.5 or 1:5. In the present invention, the solvent may include water and n-butanol, and the volume ratio of water to n-butanol may be 1:3-5; in an embodiment of the present invention, the volume ratio of water to n-butanol is 1:3, 1:4 or 1:5. In the present invention, the titanium electrode material may be a titanium anode plate, and the iridium-tantalum-titanium electrode material may be an iridium-tantalum-titanium anode material. In the present invention, the coating may be brushing. In an embodiment of the present invention, the surface of the titanium anode plate is etched with a saturated oxalic acid aqueous solution to obtain an etched rough titanium anode plate; the iridium complex, tantalum ethoxide and a solvent are mixed to obtain an iridium-tantalum mixed solution; the iridium-tantalum mixed solution is brushed on the surface of the etched rough titanium anode plate, and then baked. In the present invention, the calcination temperature can be 600-700°C, and the holding time can be 4-6h; in an embodiment of the present invention, the calcination temperature is 600°C, 625°C, 650°C, 675°C or 700°C, and the holding time is 4h, 4.5h, 5h, 5.5h or 6h. After the calcination is completed, the present invention can reduce the temperature to room temperature and take out the iridium tantalum titanium anode material. The SEM image shows that the surface of the iridium tantalum titanium anode material prepared in the embodiment of the present invention is uniform and dense, and has a polyhedral columnar structure. This polyhedral columnar structure can increase the surface area of the electrode material and increase the active sites; and because the iridium tantalum titanium anode material does not contain harmful elements such as halogens, sulfur or phosphorus, the activity, high temperature resistance and service life of the iridium tantalum titanium anode material are effectively improved.
[0041] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In the embodiment of the present invention, iridium nitrate is prepared in a reactor equipped with a reflux device, and the reactor is also equipped with a three-necked round-bottom flask, a condensing device and an exhaust gas collecting device, wherein a sodium hydroxide aqueous solution with a concentration of 30 wt% is contained in the exhaust gas collecting device;
[0043] The source of tris(oxalate)iridium(III) acid used in the embodiment is a product produced by Yunnan Precious Metals Laboratory Co., Ltd., with a chemical formula of H3Ir(C2O4) and an iridium content of 41.85%;
[0044] The source of iridium acetate is a product produced by Yunnan Precious Metals Laboratory Co., Ltd., with a chemical formula of IrO(OAc)3 and an iridium content of 48.23%;
[0045] The source of iridium triiodide is a product produced by Yunnan Precious Metals Laboratory Co., Ltd., with a chemical formula of IrI3 and an iridium content of 30.96%;
[0046] The source of iridium tetraiodide is a product produced by Yunnan Precious Metals Laboratory Co., Ltd., with a chemical formula of IrI4 and an iridium content of 26.10%;
[0047] The preparation flow chart of iridium nitrosyl nitrate is as follows Figure 1 shown.
[0048] Example 1
[0049] Weigh 5000g of tri(oxalic acid)iridium(III) acid (the mass fraction of iridium is 41.85%) and place it in a three-necked round-bottomed flask, add 3L concentrated nitric acid (6mol / L) dropwise under stirring, and introduce 10mL / min of ozone into the three-necked round-bottomed flask at the same time, and start to uniformly heat to 95°C and keep constant temperature when concentrated nitric acid starts to be added dropwise; start timing from the completion of the dropwise addition of concentrated nitric acid, reflux reaction at 95°C for 1h, and obtain iridium nitrate solution (the mass fraction of iridium nitrate is 40%). The tail gas (nitrogen oxides and carbon dioxide) generated in the reaction system enters the tail gas collection device and is absorbed by a sodium hydroxide aqueous solution with a concentration of 30wt%.
[0050] The temperature of the iridium nitrate solution was lowered to 70° C., and then 10 mL / min of NO was introduced into the iridium nitrate solution. The reaction was refluxed at 70° C. for 10 min to obtain a nitrosyl nitrate iridium solution. The nitrosyl nitrate iridium solution was evaporated and concentrated at 60° C. to obtain 4639.69 g of nitrosyl nitrate solid iridium, wherein the mass content of iridium was 45.10%, and the conversion rate of iridium was 100%.
[0051] Figure 2 is the infrared spectrum of iridium nitrosyl nitrate obtained in Example 1, Figure 2 It can be seen that 1282~1518cm -1 The absorption peak between 1110cm and 1110cm can be attributed to the absorption peak of nitrate. -1 The absorption peak at 3110 cm -1The absorption peak at can be attributed to the absorption peak of water; that is, the iridium complex containing nitrosyl, nitrate and coordinated water is prepared in the present invention.
[0052] The impurity metal content in the iridium nitrite solid obtained in Example 1 was detected by inductively coupled plasma-mass spectrometry (ICP-MS). The results are shown in Table 1.
[0053] Table 1 Content of metal element impurities and chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 1
[0054] Element Type Mass fraction (%) Element Type Mass fraction (%) Element Type Mass fraction (%) Pb <0.001 Mg <0.001 R <0.001 Fe 0.002 K <0.001 Pt <0.001 Cu 0.002 Ag <0.001 Au <0.001 Na <0.001 Pt 0.002 Mn <0.001 Ca <0.001 Pd <0.001 Co <0.001 Ni <0.001 Ti <0.001 Si 0.002 Zn <0.001 Mo <0.001
[0055] It can be seen from Table 1 that the iridium complex prepared according to the method of the present invention has high purity and basically does not introduce other metal impurities.
[0056] The chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 1 was determined by ion chromatography. The results showed that the chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 1 was 0.8 ppm, which was an extremely low concentration (and the chloride ions mainly came from the production environment and the utensils used in production), and basically would not affect the catalytic activity of the iridium catalyst prepared from iridium nitrosyl nitrate, nor would it affect the activity, high temperature resistance and service life of the iridium-containing electrode material prepared from iridium nitrosyl nitrate.
[0057] Example 2
[0058] 5000g of iridium acetate (the mass fraction of iridium is 48.23%) is weighed and placed in a three-necked round-bottomed flask. 3L concentrated nitric acid (7mol / L) is added dropwise under stirring. At the same time, 20mL / min of ozone is introduced into the three-necked round-bottomed flask. When the concentrated nitric acid starts to be added dropwise, the temperature is uniformly raised to 95°C and kept constant; the timing starts from the completion of the dropwise addition of the concentrated nitric acid, and the reaction is refluxed at 95°C for 2h to obtain an iridium nitrate solution (the mass fraction of iridium nitrate is 50%). The tail gas (nitrogen oxides and carbon dioxide) generated in the reaction system enters a tail gas collection device and is absorbed by a 30wt% sodium hydroxide aqueous solution.
[0059] The temperature of the iridium nitrate solution was lowered to 80° C., and then 20 mL / min of NO was introduced into the iridium nitrate solution. The reaction was refluxed at 80° C. for 30 min to obtain a nitrosyl nitrate iridium solution. The nitrosyl nitrate iridium solution was evaporated and concentrated at 65° C. to obtain 5331.64 g of nitrosyl nitrate solid iridium, wherein the mass content of iridium was 45.23%, and the conversion rate of iridium was 100%.
[0060] The impurity metal content in the iridium nitrite solid obtained in Example 2 was detected by inductively coupled plasma-mass spectrometry (ICP-MS). The results are shown in Table 2.
[0061] Table 2 Content of metal element impurities and chloride ion content in the iridium nitrite solid obtained in Example 2
[0062] Element Type Mass fraction (%) Element Type Mass fraction (%) Element Type Mass fraction (%) Pb <0.001 Mg <0.001 R <0.001 Fe 0.002 K <0.001 Pt <0.001 Cu 0.002 Ag <0.001 Au <0.001 Na <0.001 Ru 0.002 Mn <0.001 Ca <0.001 Pd <0.001 Co <0.001 Ni <0.001 Ti <0.001 Si 0.0015 Zn <0.001 Mo <0.001
[0063] It can be seen from Table 2 that the iridium complex prepared according to the method of the present invention has high purity and basically does not introduce other metal impurities.
[0064] The chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 2 was determined by ion chromatography. The results showed that the chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 2 was 1.1 ppm, which was an extremely low concentration (and the chloride ions mainly came from the production environment and the utensils used in production), and basically would not affect the catalytic activity of the iridium catalyst prepared from iridium nitrosyl nitrate, nor would it affect the activity, high temperature resistance and service life of the iridium-containing electrode material prepared from iridium nitrosyl nitrate.
[0065] Example 3
[0066] 5000g of iridium triiodide (the mass fraction of iridium is 30.96%) is weighed and placed in a three-necked round-bottom flask. 3L concentrated nitric acid (8mol / L) is added dropwise under stirring. When the concentrated nitric acid starts to be added dropwise, the temperature is uniformly raised to 95°C and kept constant; the timing starts from the completion of the dropwise addition of the concentrated nitric acid, and the reaction is refluxed at 95°C for 2h to obtain an iridium nitrate solution (the mass fraction of iridium nitrate is 60%). The tail gas (nitrogen oxides) generated in the reaction system enters a tail gas collection device and is absorbed by a sodium hydroxide aqueous solution with a concentration of 30wt%, and the iodine element generated in the reaction system is collected by a condensing device.
[0067] The temperature of the iridium nitrate solution was lowered to 90° C., and then 10 mL / min of NO was introduced into the iridium nitrate solution. The timing was started after the addition of NO was completed, and the reaction was refluxed at 90° C. for 20 min to obtain a nitrosyl nitrate iridium solution. The nitrosyl nitrate iridium solution was evaporated and concentrated at 70° C. to obtain 3421 g of nitrosyl nitrate solid iridium, wherein the mass content of iridium was 45.25%, and the conversion rate of iridium was 100%.
[0068] The impurity metal content in the iridium nitrite solid obtained in Example 3 was detected by inductively coupled plasma-mass spectrometry (ICP-MS). The results are shown in Table 3.
[0069] Table 3 Content of metal element impurities and chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 3
[0070]
[0071]
[0072] It can be seen from Table 3 that the iridium complex prepared according to the method of the present invention has high purity and basically does not introduce other metal impurities.
[0073] The chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 3 was determined by ion chromatography. The results showed that the chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 3 was 1.1 ppm, and the iodide ion content was 1.3 ppm, which were extremely low in concentration (and the chloride ions mainly came from the production environment and the utensils used in production, and the iodide ions mainly came from the raw material iridium triiodide), which basically would not affect the catalytic activity of the iridium catalyst prepared from iridium nitrosyl nitrate, nor would it affect the activity, high temperature resistance and service life of the iridium-containing electrode material prepared from iridium nitrosyl nitrate.
[0074] Example 4
[0075] 5000g of iridium tetraiodide (the mass fraction of iridium is 26.10%) is weighed and placed in a three-necked round-bottom flask. 3L concentrated nitric acid (8mol / L) is added dropwise under stirring. When the concentrated nitric acid starts to be added dropwise, the temperature is uniformly raised to 95°C and kept constant; the timing starts from the completion of the dropwise addition of the concentrated nitric acid, and the reflux reaction is carried out at 95°C for 1.5h to obtain an iridium nitrate solution (the mass fraction of iridium nitrate is 50%). The tail gas (nitrogen oxides) generated in the reaction system enters the tail gas collection device and is absorbed by the sodium hydroxide aqueous solution with a concentration of 30wt%, and the iodine element generated in the reaction system is collected by a condensing device.
[0076] The temperature of the iridium nitrate solution was lowered to 90° C., and then 20 mL / min of NO was introduced into the iridium nitrate solution. The timing was started after the addition of NO was completed, and the reaction was refluxed at 90° C. for 10 min to obtain a nitrosyl nitrate iridium solution. The nitrosyl nitrate iridium solution was evaporated and concentrated at 70° C. to obtain 2887.80 g of nitrosyl nitrate solid iridium, wherein the mass content of iridium was 45.19%, and the conversion rate of iridium was 100%.
[0077] The impurity metal content in the iridium nitrite solid obtained in Example 4 was detected by inductively coupled plasma-mass spectrometry (ICP-MS). The results are shown in Table 4.
[0078] Table 4: Content of metal element impurities and chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 4
[0079]
[0080]
[0081] It can be seen from Table 4 that the iridium complex prepared according to the method of the present invention has high purity and basically does not introduce other metal impurities.
[0082] The chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 4 was determined by ion chromatography. The results showed that the chloride ion content in the iridium nitrosyl nitrate solid obtained in Example 4 was 1.1 ppm, and the iodide ion content was 1.8 ppm, which were extremely low in concentration (and the chloride ions mainly came from the production environment and the utensils used in production, and the iodide ions mainly came from the raw material iridium tetraiodide), which basically would not affect the catalytic activity of the iridium catalyst prepared from iridium nitrosyl nitrate, nor would it affect the activity, high temperature resistance and service life of the iridium-containing electrode material prepared from iridium nitrosyl nitrate.
[0083] Example 5
[0084] Take a titanium anode plate, etch the surface of the titanium anode plate with a saturated oxalic acid aqueous solution to obtain an etched rough titanium anode plate. Take 10g of the iridium nitrosyl nitrate solid obtained in Example 1, 15g of tantalum ethanol, 10mL of water and 30mL of n-butanol to obtain an iridium-tantalum mixed solution. Apply the iridium-tantalum mixed solution to the surface of the etched titanium anode plate, and then calcine it at a constant temperature of 600°C for 5h. After the calcination, lower the temperature to room temperature to form an iridium-tantalum composite film layer on the surface of the etched titanium anode plate to obtain an iridium-tantalum-titanium anode material.
[0085] The surface morphology of the iridium-tantalum-titanium anode material obtained in Example 5 was observed by scanning electron microscopy. Figure 3 As shown, Figure 3 (A) is a SEM image of an iridium-tantalum-titanium anode material (scale bar is 20 μm), and (B) is a SEM image of an iridium-tantalum-titanium anode material (scale bar is 500 nm). Figure 3 It can be seen that the surface of the iridium tantalum titanium anode material is uniform and dense, and has a polyhedral columnar structure. This polyhedral columnar structure can increase the surface area of the electrode material, increase the active sites, and improve the activity, high temperature resistance and service life of the electrode material.
[0086] In summary, the present invention prepares iridium nitrate solution, iridium nitrite nitrate solution and solid iridium nitrite nitrate which are substantially free of other metal impurities and harmful elements such as halogens, sulfur and phosphorus. The preparation method is simple and efficient, suitable for industrial mass production, and can be used to prepare iridium tantalum titanium anode materials.
[0087] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing an iridium complex, characterized in that: The following steps are involved: Mixing an iridium-containing compound with concentrated nitric acid and performing an oxidation treatment to obtain an iridium nitrate solution; the iridium-containing compound includes an organic iridium complex or iridium iodide; NO is introduced into the iridium nitrate solution to carry out coordination reaction to obtain the iridium complex; the iridium complex contains iridium ions, nitrosyl groups and nitrate groups; the flow rate of NO is 10-20 mL / min.
2. The preparation method according to claim 1, characterized in that: The organic iridium complex comprises at least one of tri(oxalato)iridium(III) acid, iridium acetate and iridium acetylacetonate; and the iridium iodide is iridium triiodide or iridium tetraiodide.
3. The preparation method according to claim 1, characterized in that: The concentration of the concentrated nitric acid is 6-8 mol / L; the usage ratio of the iridium-containing compound to the concentrated nitric acid is 5000 g: 3-5 L.
4. The preparation method according to claim 1, characterized in that: The oxidation treatment is carried out at a temperature of 90 to 100° C. and for a time of 1 to 2 hours.
5. The preparation method according to claim 1 or 4, characterized in that: When the iridium-containing compound is an organic iridium complex, the oxidation treatment is carried out in an O3 atmosphere, and the flow rate of O3 is 10 to 30 mL / min.
6. The preparation method according to claim 1, wherein the mass fraction of the iridium nitrate solution is 40-60%; the temperature of the coordination reaction is 70-90°C, and the time is 10-30 minutes.
7. The iridium complex obtained by the preparation method according to any one of claims 1 to 6; the iridium complex is iridium nitrosyl nitrate, and its chemical formula is Ir(NO)(NO3)3(H2O)2.
8. Use of the iridium complex according to claim 7 in catalysts or electrode materials.
9. An iridium-tantalum-titanium electrode material, comprising a titanium electrode material and an iridium-tantalum composite film layer on the surface of the titanium electrode material; the surface of the iridium-tantalum composite film layer has a polyhedral columnar structure; the iridium-tantalum composite film layer is obtained by mixing an iridium complex and tantalum ethoxide and then calcining, and the iridium complex is the iridium complex described in claim 7.
10. The iridium-tantalum-titanium electrode material according to claim 9, characterized in that: The mass ratio of the iridium complex to tantalum ethoxide is 1:3-5; the calcination temperature is 600-700°C, and the heat preservation time is 4-6h.